2022
DOI: 10.3389/fpubh.2022.860264
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Dimensions of Professional Burnout and Turnover Intention Among Nurses Working in Hospitals During Coronavirus Disease (COVID-19) Pandemic in Iran Based on Structural Model

Abstract: PurposeThis study was done to assess the dimensions of professional burnout and turnover intention among nurses working in hospitals during the coronavirus disease 2019 (COVID-19) pandemic in Iran based on a structural model.MethodsThis cross-sectional study was performed among 170 nurses working in two referral hospitals of COVID-19 in Tehran Province, Iran, from September to December 2020. Data were collected using the sociodemographic form, Maslach Burnout Inventory (MBI), and Turnover Intention Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Also, this study confirms that male HCPs intent to leave their profession than females; these findings are congruent with a previous conclusion 38 . On the other hand, some studies found no relationship between the intent HCPs to leave the job and their socio‐demographic variables 39,40 …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Also, this study confirms that male HCPs intent to leave their profession than females; these findings are congruent with a previous conclusion 38 . On the other hand, some studies found no relationship between the intent HCPs to leave the job and their socio‐demographic variables 39,40 …”
Section: Discussionsupporting
confidence: 90%
“… 38 On the other hand, some studies found no relationship between the intent HCPs to leave the job and their socio‐demographic variables. 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes the head nurse most personally aware of the management of the leadership relationship and they possess the maximum experience which contributes to their high sense of psychological safety. Additionally, for head nurses and above, their sense of personal achievement was also acquired at work; personal achievement is a predictor of nurses’ turnover intention ( Karimi et al, 2022 ). When a person’s social status, personal income, and sense of achievement is acquired at work, they have a strong sense of belonging and identity toward the organization, higher psychological ownership, and lower turnover intention.…”
Section: Discussionmentioning
confidence: 99%
“…Nurse turnover rates in several a uent countries, such as Australia, the United States, and New Zealand, range from 15.1-44.3% [2]. The turnover rate for newly graduating nurses in Korea is 42.7% [3], whereas in China, which has a severe shortage of nurses, the rates are as high as 59.6% and 79.4% in April and August of the rst year, respectively, and 71.8% of newly graduated nurses tend to quit their jobs within the rst year [4].Moreover, psychological issues during COVID-19 led several nurses to resign or reevaluate their career choices [5]. The di culties are signi cantly greater for newly graduated nurses in this circumstance [6].According to a study [7], to ease the nursing workface shortage, guarantee a su cient and quali ed future workforce, and stabilize the nursing workforce, particular consideration should be given to freshly graduated nurses and their well-being.…”
mentioning
confidence: 99%